RENCANA ANGGARAN BIAYA MENGGUNAKAN METODE AHSP 2016 DAN SNI 2018 PADA PROYEK PEMBANGUNAN GEDUNG MADRASAH IBTIDAIYAH NEGERI 5 KABUPATEN MALUKU TENGAH - Endom, Saryo Theo; Saleh, La Mohamat; Titaley, Henriette Dorothy (Jurusan Teknik Sipil, 2023)
A project is a unique activity with a set goal with limited time to be able to reach a specified target. Within the arrangement of a construction project, cost estimates play a significant role. The greater the value of a construction project causes the need for resources to manage the work. Therefore, it requires careful, carefully structured cost planning according to the method of analysis used. The SNI method was a renewal from the 1921 BOW analysis (Burgeslijke Openbare Werken) issued by the residential research and development center.The AHSP method (Job Unit Price Analysis) isa guide for analysis issued by the ministry of public work and citizen housing (PUPR). The aim of thi s study is to get results from economical cost-spending estimates between methods. According to estimates of the cost budget using the AHSP 2016 method, Rp 2,891,000,000 and according to estimates of the cost budget using the SNI 2018 method, Rp 2.615.500.000 by profit from AHSP 2016 and SNI 2018, Rp 275,500,000. And a 9.53% percentage presentation.